Effects of Hematopoietic Cell Transplantation on the Pulmonary Immune Response to Infection - Zinter, Matt S.; Hume, Janet R. (Frontiers in Pediatrics, 2021)
Pulmonary infections are common in hematopoietic cell transplant (HCT) patients of all ages and are associated with high levels of morbidity and mortality. Bacterial, viral, fungal, and parasitic pathogens are all represented as causes of infection. The lung mounts a complex immune response to infection and this response is significantly affected by the pre-HCT conditioning regimen, graft characteristics, as well as ongoing immunomodulatory therapy. We review the published literature, including animal models as well as human data, to describe what is known about the pulmonary immune response to infection in HCT recipients. Studies have focused on the pulmonary immune response to Aspergillus fumigatus, gram-positive and gram-negative bacteria, and viruses, and show a range of defects associated with both the innate and adaptive immune responses after HCT. There are still many open areas for research, to delineate novel therapeutic targets for pulmonary infections as well as to explore linkages between infection and non-infectious inflammatory lung conditions such as idiopathic pneumonia syndrome associated with HCT.